Tiger - Stone, Jeff (New York : Yearling, 2006)
Twelve-year-old Fu and his temple brothers Malao, Seh, Hok, and Long don$1 (Bt know who their parents were. Raised from infancy by their grandmaster, they think of their temple as their home and their fellow warrior monks$1 (Btheir (3z(Btemple brothers(3y$1 (Bas their family. Then one terrible night, the temple is destroyed. Fu and his brothers are the only survivors. Charged by their grandmaster to uncover the secrets of their past, the five flee into the countryside and go their separate ways.s
Keywords: Martial arts -- Fiction; Action and adventure fiction